2021
DOI: 10.1109/tit.2020.2980818
|View full text |Cite
|
Sign up to set email alerts
|

How to Construct Mutually Orthogonal Complementary Sets With Non-Power-of-Two Lengths?

Abstract: Mutually orthogonal complementary sets (MOCSs) have received significant research attention in recent years due to their wide applications in communications and radar. Existing MOCSs which are constructed based on generalized Boolean functions (GBFs) mostly have lengths of power-of-two. How to construct MOCSs with non-power-of-two lengths whilst having large set sizes is a largely open problem. With the aid of GBFs, in this paper, we present new constructions of such MOCSs and show that the maximal achievable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…be the binary representations of g, h, i, and j, respectively. Then, four cases are considered as follows to prove (29).…”
Section: A Gcaps Based On Generalized Boolean Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…be the binary representations of g, h, i, and j, respectively. Then, four cases are considered as follows to prove (29).…”
Section: A Gcaps Based On Generalized Boolean Functionsmentioning
confidence: 99%
“…The construction from generalized Boolean functions has algebraic structure and hence can be friendly for efficient hardware generations. Since then, there have been a number of literature investigating constructions of 1-D sequences from Boolean functions, including GCSs [9], [21]- [25], complete complementary codes (CCCs) [26]- [29]. Zcomplementary pairs (ZCPs) [30]- [35], and Z-complementary sets (ZCSs) [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…Considering C = {C 0 , C 1 , C 2 , C 3 } as a (4, 4, N )-CCC, the search results can be found in Table III, where each element represents a power of (−1). The search results are important in itself, because in recent results [23]- [25], we observe that for a (K, M, N ) mutually orthogonal sequence set, through systematic construction, the maximum achievable K/M ratio is 1/2, when N is not in the form of 2 m . However, for our case, although N is not in the form of power-of-two, since the sequence sets are CCC (i.e., K = M ), the K/M ratio is 1.…”
Section: Let Us Definementioning
confidence: 99%
“…, CCCs [19], [20], mutually orthogonal complementary sets (MOCSs) [21], ZCZ sequence sets [22]- [25], nearcomplementary sequences [26], [27], multiple-shift complementary sequences [12], and ZCCSs [28]- [31]. The constructed sequence sets from Boolean functions often lead to sequences of power-of-two length.…”
mentioning
confidence: 99%
“…The constructed sequence sets from Boolean functions often lead to sequences of power-of-two length. In [14]- [17], [21], it was shown that Boolean functions can also be useful to construct GCSs and MOCSs of non-power-of-two length. Recently, a construction of ZCCSs with non-power-of-two length based on Boolean functions was proposed in [31].…”
mentioning
confidence: 99%